Identification of fatigue and mechanical characteristics of explosively welded steel - titanium composite (Fracture and Structural Integrity, 2017)
Paper presents results of fatigue tests performed on S355J2 steel - titanium Grade 1 composite produced in explosive welding technology. Specimens were subjected to cyclic tension-compression loading with zero mean value and controlled force. Also mechanical properties were investigated.
Keywords: Welding; Fatigue; Explosive; Bimetal; Steel; Titanium